2016
DOI: 10.5483/bmbrep.2016.49.6.240
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of nuclear interactome of C-terminal domain small phosphatase-like 2 using inducible expression system and shotgun proteomics

Abstract: RNA polymerase II C-terminal domain phosphatases are newly emerging family of phosphatases that contain FCPH domain with Mg+2-binding DXDX(T/V) signature motif. Its subfamily includes small CTD phosphatases (SCPs). Recently, we identified several interacting partners of human SCP1 with appearance of dephosphorylation and O-GlcNAcylation. In this study, using an established cell line with inducible CTDSPL2 protein (a member of the new phosphatase family), proteomic screening was conducted to identify binding pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(35 reference statements)
2
3
0
Order By: Relevance
“…In accord with prior studies (Kemmer et al, 2006;Zhao et al, 2014;Kang et al, 2016), we found that SCP4 was localized to the nucleus of AML cells (Figure 4A). However, our efforts at performing SCP4 chromatin immunoprecipitation sequencing (ChIP-seq) in MOLM-13 cells failed to identify evidence of sequence-specific DNA occupancy (data not shown).…”
Section: Stk35 and Pdik1l Bind Selectively To The Catalytically Active Form Of Scp4supporting
confidence: 92%
“…In accord with prior studies (Kemmer et al, 2006;Zhao et al, 2014;Kang et al, 2016), we found that SCP4 was localized to the nucleus of AML cells (Figure 4A). However, our efforts at performing SCP4 chromatin immunoprecipitation sequencing (ChIP-seq) in MOLM-13 cells failed to identify evidence of sequence-specific DNA occupancy (data not shown).…”
Section: Stk35 and Pdik1l Bind Selectively To The Catalytically Active Form Of Scp4supporting
confidence: 92%
“…In accord with prior studies (Kemmer et al, 2006;Zhao et al, 2014;Kang et al, 2016), we found that SCP4 was localized to the nucleus of AML cells (Figure 4A). However, our efforts at performing SCP4 ChIP-seq in MOLM-13 cells failed to identify evidence of sequence-specific DNA occupancy (data not shown).…”
Section: Stk35 and Pdik1l Bind Selectively To The Catalytically Active Form Of Scp4supporting
confidence: 92%
“…Coimmunoprecipitation analysis was performed as described previously [ 41 ]. In brief, 500 μg of cellular proteins were incubated with immunoprecipitating antibodies in extraction buffer for 6 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%